Spatial patterns and drivers of carbon emissions in metropolitan peripheries - Kailin, Zhang; Tingting, Ma; Jiajun, Yi; Huafen, Xing; Kaichun, Zhou (Frontiers in Environmental Science, 2026)
Understanding the spatial patterns and determinants of carbon emission efficiency (CEE) is essential for advancing regional low-carbon development. While existing studies focus primarily on metropolitan cores, much less is known about peri-metropolitan regions and how core cities influence their surrounding areas. To address this gap, we assess the spatio-temporal evolution of CEE in the peri-metropolitan region of Chang-Zhu-Tan, China, and identify its key drivers. The results show that, despite an overall improvement in CEE, significant core–periphery disparities and pronounced intra-periphery heterogeneity persist. The Spatial Durbin Model, estimated with two-way fixed effects, reveals significant spatial spillovers and shows that GDP growth, population density, and core–periphery economic linkages are the primary factors shaping CEE variation. These findings provide a spatially explicit perspective on carbon emission efficiency in peri-metropolitan regions and offer empirical evidence for designing differentiated low-carbon policies within metropolitan systems.